(18)F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Findings of Pancreatic Hemangiopericytoma - Ustun, Funda (Indian J Nucl Med, 2017)
A 42-year-old woman with a large pancreatic tumor had undergone (18)F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) imaging. Moderate metabolic activity was detected on the head of the pancreas. The tumor was resected and it was histopathologically diagnosed as malign pancreatic hemangiopericytoma (HPC). HPC is a rare soft tissue sarcoma. The tumor is considered aggressive with high rates of local recurrence and metastasis regardless the localization. Herein, we present the imaging characteristics of HPC with (18)F-FDG PET/CT.